Influência do tempo de moagem na potencialidade de incorporação do resíduo de cerâmica vermelha em solo cimento - Oliveira, Maria Alanya da Costa de (Universidade Federal Rural do Semi-Árido, 2019)
The advance of civil construction in recent years has been important for the development of cities and also for economy, but in parallel with this high demand, has compulsively increased the amount of waste generation. In this sense, the search for sustainable alternatives has been a challenge for Civil Engineers because in addition to seeking to reduce natural resources, the intention goes further, that is, to reuse the materials that can be recycled. The aim of this work was to analyze the behavior of the insertion of this residue in the composition of the soil-cement by varying the time of grinding, discussing its properties and characteristics to be applied in construction products. A priori, bibliographical research was done on the subject, including the relation of disposal to the environment. With the materials in hand, tests were carried out for both soil-cement and soil-cement with the addition of RCV in order to characterize them as: granulometry test, specific mass and compaction. Complementing the research, tests of compressive strength were carried out by analyzing the soil-cement behavior at different dosages, such as 0% and 20% of RCV at different grinding times ie 9, 12 e 15 min. During the study it was observed that the recycled RCV has characteristics of an aggregate, so that the addition of the residue in the soil-cement mixture caused a decrease in the apparent maximum dry mass as the humidity increased. It was also noticed an increase in the value of the compressive strength of the samples with the residue in relation to without the residue, in all the samples the increase was in more than 50% with respect to the initial sample, that is, without the RCV, among the 3 samples that had the highest increase was the time equal to 15min of milling, with approximately 60% increase of the resistance. Therefore, the addition of the RCV provides better performance to the elements of the soil-cement composition and promotes environmental benefits by reducing the material discarded. Therefore, it is recommended to perform other studies with other dosages in order to compare the results with those already confirmed, in order to find values with more resistance and more quality.
Monografia
Keywords: Material cerâmico; resistência a compressão; desenvolvimento sustentável; impacto ambiental; construção civil; ceramic material; compressive strength; sustainable development; environmental; ENGENHARIAS::ENGENHARIA CIVIL